Practical RichFaces - Katz, Max (Apress : Imprint: Apress, 2008)
JBoss RichFaces is a rich JavaServer Faces (JSF) component library that helps developers quickly develop next-generation web applications. Practical RichFaces describes how to best take advantage of RichFaces, the integration of the Ajax4jsf and RichFaces libraries, to create a flexible and powerful programs. Assuming some JSF background, it shows you how you can radically reduce programming time and effort to create rich Ajax-based applications.